Uruguay Round, World Trade Organization, and the problem of regulating international economic behaviour - Jackson, John H. (Centre for Trade Policy and Law OttawaCA, 1994)
Looks at the Uruguay Round results and achievements and focuses on the World Trade Organisation and the new dispute settlement rules. Discusses the future and emerging challenges to the trading system. Suggests some directions for a framework for policy analysis. Looks at constitution making and world trade institutions and makes conclusions.